If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -26 = 10 Reorder the terms: -26 + x = 10 Solving -26 + x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + x = 10 + 26 Combine like terms: -26 + 26 = 0 0 + x = 10 + 26 x = 10 + 26 Combine like terms: 10 + 26 = 36 x = 36 Simplifying x = 36
| 2x-2=-4(x-4) | | 10-3*x=x+4 | | -9=6+5v | | 3y+7=5y+1 | | 32x+(-32x+25)=12 | | 142,000,000/1.19 | | 12x-20=7x+20 | | f(20)=0.05x+3 | | 9c-4=26-c | | 50=5(3m-2) | | -15(-B)= | | 1/4=2/x | | -42=4t | | d/5-3=-4 | | 7+3t=5t-1 | | -0.6k-1+0.5k=3 | | g/10=10 | | 4x+-5y=-12 | | 276/6 | | 6c-3c+2d-4d= | | 2m+4=m-10 | | 0=x^2-20x+100 | | 5h/3=15 | | bxA=c | | 13x-6=4(3x+2)-2 | | 150,000,000/1.18=1.18N/1.18 | | y=42x+15 | | -33=2(v-6)-5v | | a+a.32=-325 | | (x+2)*(x+2)=14 | | -7x=6+3 | | 7/10=n/6 |